Costs and outcomes of increasing access to bariatric surgery for obesity: cohort study and cost-effectiveness analysis using electronic health records - Martin C Gulliford; Judith Charlton; Helen P Booth; Alison Fildes; Omar Khan; Marcus Reddy; Mark Ashworth; Peter Littlejohns; A Toby Prevost; Caroline Rudisill (National Institute for Health Research, 2016)
Background: Bariatric surgery is known to be an effective treatment for extreme obesity but access to these procedures is currently limited. Objective: This study aimed to evaluate the costs and outcomes of increasing access to bariatric surgery for severe and morbid obesity. Design and methods: Primary care electronic health records from the UK Clinical Practice Research Datalink were analysed for 3045 participants who received bariatric surgery and 247,537 general population controls. The cost-effectiveness of bariatric surgery was evaluated in severe and morbid obesity through a probabilistic Markov model populated with empirical data from electronic health records. Results: In participants who did not undergo bariatric surgery, the probability of participants with morbid obesity attaining normal body weight was 1 in 1290 annually for men and 1 in 677 for women. Costs of health-care utilisation increased with body mass index category but obesity-related physical and psychological comorbidities were the main drivers of health-care costs. In a cohort of 3045 adult obese patients with first bariatric surgery procedures between 2002 and 2014, bariatric surgery procedure rates were greatest among those aged 35-54 years, with a peak of 37 procedures per 100,000 population per year in women and 10 per 100,000 per year in men. During 7 years of follow-up, the incidence of diabetes diagnosis was 28.2 [95% confidence interval (CI) 24.4 to 32.7] per 1000 person-years in controls and 5.7 (95% CI 4.2 to 7.8) per 1000 person-years in bariatric surgery patients (adjusted hazard ratio was 0.20, 95% CI 0.13 to 0.30; p < 0.0001). In 826 obese participants with type 2 diabetes mellitus who received bariatric surgery, the relative rate of diabetes remission, compared with controls, was 5.97 (95% CI 4.86 to 7.33; p < 0.001). There was a slight reduction in depression in the first 3 years following bariatric surgery that was not maintained. Incremental lifetime costs associated with bariatric surgery were £15,258 (95% CI £15,184 to £15,330), including costs associated with bariatric surgical procedures of £9164 per participant. Incremental quality-adjusted life-years (QALYs) were 2.142 (95% CI 2.031 to 2.256) per participant. The estimated cost per QALY gained was £7129 (95% CI £6775 to £7506). Estimates were similar across gender, age and deprivation subgroups. Limitations: Intervention effects were derived from a randomised trial with generally short follow-up and non-randomised studies of longer duration. Conclusions: Bariatric surgery is associated with increased immediate and long-term health-care costs but these are exceeded by expected health benefits to obese individuals with reduced onset of new diabetes, remission of existing diabetes and lower mortality. Diverse obese individuals have clear capacity to benefit from bariatric surgery at acceptable cost. Future work: Future research should evaluate longer-term outcomes of currently used procedures, and ways of delivering these more efficiently and safely. Funding: The National Institute for Health Research (NIHR) Health Services and Delivery Research programme. Martin C Gulliford and A Toby Prevost were supported by the NIHR Biomedical Research Centre at Guy's and St Thomas' Hospitals. Peter Littlejohns was supported by the South London Collaboration for Leadership in Applied Health Research and Care. The funders did not engage in the design, conduct or reporting of the research.